The marginal teacher a step-by-step guide to fair procedures for identification and dismissal - Lawrence, C. Edward; Sage eBooks (Thousand Oaks, Calif. : Corwin, 2005)
'The Marginal Teacher' offers solutions to the problem of unproductive teachers, illustrating the proper actions that headteachers should integrate into the evaluation processes to gather documentation to help improve or terminate an ineffective teacher.
Includes bibliographical references and index.
Specialized.
System requirements for accompanying disc: For Windows or Macintosh.
Description based on print version record.
Keywords: Teachers -- Rating of -- United States; Teachers -- Dismissal of -- United States; Electronic books